2017
DOI: 10.1007/s11999-016-5153-0
|View full text |Cite
|
Sign up to set email alerts
|

Do Needleless Knots have Similar Strength as the Krackow Suture? An In Vitro Porcine Tendon Study

Abstract: Background Numerous needleless techniques for tendon graft fixation that feature several advantages have been reported. However, there are few studies that have compared the holding strength between the needleless techniques (rolling hitch and modified rolling hitch) and traditional suture methods. Questions/purposes To compare the tendon graft-holding strength of the rolling hitch and modified rolling hitch with the Krackow stitch in an in vitro porcine biomechanical model. Methods Thirty fresh-frozen porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…A secure suture-tendon construct is especially important when a post tie fixation technique is used because the mitigating construct may potentially lead to graft loosening and affect graft healing. Numerous biomechanical studies have been conducted to obtain reliable suture-tendon constructs, 1 , 3 , 4 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 and using the Krackow suture technique accompanied with a high-tensile strength suture is currently the most popular method. Recently, a high-tensile strength tape was developed, which was reported to have greater knot security, ultimate load to failure, and tensile stiffness as compared to the high-tensile strength round core suture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A secure suture-tendon construct is especially important when a post tie fixation technique is used because the mitigating construct may potentially lead to graft loosening and affect graft healing. Numerous biomechanical studies have been conducted to obtain reliable suture-tendon constructs, 1 , 3 , 4 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 and using the Krackow suture technique accompanied with a high-tensile strength suture is currently the most popular method. Recently, a high-tensile strength tape was developed, which was reported to have greater knot security, ultimate load to failure, and tensile stiffness as compared to the high-tensile strength round core suture.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters in the biomechanical testing protocol were in accordance to previous studies. 1,4,9,[15][16][17][18][19][20][21] All specimens were initially pretensioned to 100 N at a rate of 100 mm/min for 3 cycles and then preloaded to 50 N for 1 minute. After that, each specimen was cyclically loaded between 50 and 200 N with a cross-head speed of 200 mm/min for 200 cycles.…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…3,4,13 It is clearly not the quickest approach and the desire for a more efficient yet effective option has led to the development of many other stitch configurations. 1,6,8,14 The goals of a simpler and quicker construct are achieved by the SpeedTrap, WhipKnot, and Loop-in-loop constructs. Additionally considering tissue damage during the load to failure testing demonstrates that these three techniques are the least traumatic of those tested.…”
Section: Discussionmentioning
confidence: 99%
“…2 Hong et al found no difference in cyclic load and load to failure between needleless knot techniques and Krackow configurations. 6 Ostrander et al found no difference to elongation in cyclic load between modified Krackow and modified locking Speedwhip stitch. 7 Gnandt et al show during a single load to failure that highetensile strength tape performs more favorably than highetensile strength suture, with a greater mean load to failure, in both the whip-and Krackow-stitch models.…”
Section: See Related Article On Page 663mentioning
confidence: 96%